Near-field scattering from PEC wedge excited by electric dipole in lossy medium - Ozturk, Hulya; Yegin, Korkut (Emerald Group Publishing Ltd, 2021)
Purpose The purpose of this paper is to derive the dyadic representations of Green's function in lossy medium because of the electric current dipole source radiating in close proximity of a PEC wedge and to reveal the effect of conductivity on the scattered electric field. Design/methodology/approach By using the scalarization procedure, the paraxial fields are obtained first and then scalar Green's functions are used to derive asymptotic forms of the dyadic Green's functions. The problem is also analyzed by the image theory and analytical derivations are compared. However, analytically calculated results are validated with FEKO, a commercially available numerical electromagnetic field solver. Findings The results indicate that excellent agreement is observed between analytical and numerical results. Moreover, it is found that the presence of conductivity introduces a reduction in scattered electric fields. Originality/value Asymptotically derived forms presented in this study can be used to calculate field distributions in the paraxial region of a wedge in a lossy medium.
Keywords: Electromagnetic fields; Electromagnetic waves; Electromagnetic scattering; PEC wedge; Point current source; Dyadic green's functions; Paraxial region